Systematic review and meta-analysis of PD-L1 expression discordance between primary tumor and lung cancer brain metastasis. Issue 1 (10th November 2021) - Tonse, Raees; Rubens, Muni; Appel, Haley; Tom, Martin C; Hall, Matthew D; Odia, Yazmin; McDermott, Michael W; Ahluwalia, Manmeet S; Mehta, Minesh P; Kotecha, Rupesh
Abstract: Background: Novel immunotherapeutic strategies targeting the programmed cell death protein 1 (PD-1)/programmed death-ligand 1 (PD-L1) axis are often administered when metastatic tumors show PD-L1 positivity, even in the setting of lung cancer brain metastasis (LCBM). However, biological differences exist between primary tumors and metastatic sites. The objective of this study was to analyze rates of PD-L1 receptor discordance between primary tumors and LCBM. Methods: A systematic review of studies of biopsied or resected LCBM evaluating PD-L1 discordance published in the Medline database was performed using PRISMA guidelines. Weighted random effects models were used to calculate pooled estimates. Results: Six full-text articles ( n = 230 patients) with a median of 32 patients in each study (range: 24–73) reported PD-L1 receptor expression analyses of both primary lung tumors and brain metastases and met inclusion criteria. The pooled estimate for tumor cell (TC) PD-L1 receptor discordance between primary tumors and LCBM was 19% (95% confidence interval [CI]: 10–27%). For PD-L1 receptor expression in tumor-infiltrating lymphocytes (TIL), the weighted pooled estimate for discordance was 21% (95% CI: 8–44%). For primary versus LCBM, the positive rates by expression levels of <1%, 1–50%, and >50% were 52% (95% CI: 30–73%) versus 56% (95% CI: 34–76%), 30% (95% CI: 22–40%) versus 20% (95% CI: 10–35%), and 15% (95% CI: 6–36%) versus 22% (95% CI: 15–31%) ( P = .425), respectively. Conclusions: PD-L1 discordance occurs in ~20% of LCBM, with the greatest discordance in the 1–50% expression category. Although controversial, confirming discordance might be important for selection of immune checkpoint inhibitor therapy and in the analysis of patterns of failure after treatment.